2013
DOI: 10.12659/aob.883848
|View full text |Cite
|
Sign up to set email alerts
|

Techniques frequently used during London Olympic judo tournaments: a biomechanical approach

Abstract: Feedback between training and competition should be considered in athletic training. The aim of the study was contemporary coaching tendencies in women's and men's judo with particular focus on a biomechanical classification of throws and grappling actions. 359 throws and 77 grappling techniques scored by male and female athletes in Olympic Judo Tournaments (London 2012) have been analyzed. Independence of traits (gender and weight category by technique classes) was verified via c 2 test. Comparison between fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 6 publications
4
52
3
1
Order By: Relevance
“…Indeed, a biomechanical analysis of judo techniques revealed that both men and women use similar techniques in contemporary Olympic tournaments 37. However, women seem to be more exposed during ground fight,14 where their injuries are frequently derived from arm lock techniques 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a biomechanical analysis of judo techniques revealed that both men and women use similar techniques in contemporary Olympic tournaments 37. However, women seem to be more exposed during ground fight,14 where their injuries are frequently derived from arm lock techniques 14.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Seoi Nage techniques, that is, the throws with ‘lever applied with variable arm’,37 were supposed to be high-risk techniques for shoulder injuries being thrown,15 and for knee injuries performing the throw26 in all age categories and for both genders 19. However, results on the frequency of knee injuries while performing this technique are discordant 38.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we found that male athletes had more level I injuries, female athletes had more level II injuries, while male and female athletes had similar risk of level III injuries (P=0.003). Sterkowicz et al 31 suggested that such sex-specific differences are related to physical build, as athletes tend to adapt their strategy and use different skill sets according to their physical build and strength relative to those of their opponent.…”
Section: Discussionmentioning
confidence: 99%
“…We also noted that male athletes displayed a higher annual injury rate than female athletes, most likely due to athletes tending to adapt their strategy and using different skill sets according to their physical build and strength 27. Additionally, male athletes have higher anaerobic power than female athletes and engage in more risk-taking 28.…”
Section: Discussionmentioning
confidence: 73%